An Efficient Cooperative Medium Access Control Protocol for Wireless IoT networks in Smart World System. (1st May 2019) - Mahmud, Md. Tareq; Rahman, Md. Obaidur; Hassan, Mohammad Mehedi; Almogren, Ahmad; Zhou, Mengchu
Abstract: In recent years, the Internet of Things (IoT) has become the key enabler for Smart World System (SWS). In SWS environment, the IoT is empowering wireless devices/objects with abilities of sensation and communication with each other via Internet and providing simplified, more efficient, and enjoyable lifestyle. However, efficient communication between various wireless devices in IoT network is very important, especially in long distant wireless transmission case. Cooperative Medium Access Control (MAC) protocols for wireless networks supporting the IoT is becoming popular to handle this issue. It considers several metrics, e.g., SNR (Signal to Noise Ratio), delay and residual energy. Nowadays, distance metric has appended a new dimension in the relay selection metric list for Cooperative MAC. Howsoever, protocols that have used distance metric can be optimized further in selecting a relay node by considering reliability. Hence, targeting to optimize relay selection for designing a cooperative MAC protocol, we have proposed a Reliability-based Distance-aware Data-rate-adaptive Cooperative MAC for wireless IoT networks. For the assurance of unfailing and cooperative data transmission, this work strengthens the most suitable relay node selection using a cooperative reliability factor. Distance and residual energy are also used to ascertain that the position of optimal relay possess superior rates. Extensive simulation results demonstrate that proposed reliability-based optimal relay selection as well as MAC operation significantly improves the performance over the existing ones.